2018
DOI: 10.5152/eurjrheum.2018.18036
|View full text |Cite
|
Sign up to set email alerts
|

IL1-blocking therapy in colchicine-resistant familial Mediterranean fever

Abstract: ObjectiveApproximately 10%–20% of patients with familial Mediterranean fever (FMF) show an inadequate response to colchicine. In our cohort study, patients with FMF with or without amyloidosis and with an inadequate response to colchicine were treated with anakinra or canakinumab.MethodsClinical and laboratory parameters, Mediterranean fever (MEFV) mutations, and patient-reported outcomes were analyzed in 31 patients treated with anakinra or canakinumab.ResultsIn a cohort of 250 adult patients with FMF, 31 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
29
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 32 publications
6
29
0
2
Order By: Relevance
“…Moreover, the serum acute phase reactants of these patients returned to normal levels [10]. Kohler et al achieved a 90% FMF-50 score with IL-1blocking therapy in 31 FMF patients [11]. In our study, we achieved a 96% FMF-50 response rates for the anti-IL-1 treatments, which is similar to previous studies.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, the serum acute phase reactants of these patients returned to normal levels [10]. Kohler et al achieved a 90% FMF-50 score with IL-1blocking therapy in 31 FMF patients [11]. In our study, we achieved a 96% FMF-50 response rates for the anti-IL-1 treatments, which is similar to previous studies.…”
Section: Discussionsupporting
confidence: 90%
“…Local reactions with anakinra are reported in 25% of patients, which were transient and tolerable. In this study, the quality of life in patients treated with canakinumab was better than anakinra due to daily injection 23. In our study, local reactions with anakinra and headache were more frequent, whereas these side effects were not observed in canakinumab.…”
supporting
confidence: 41%
“…Recently, studies have shown that anti-IL-1 treatment is effective and safe in children with FMF. 22 Köhler et al 23…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Significant reasons to prescribe anakinra rather than canakinumab are the price and/or reimbursement conditions of the drugs, explaining probably partially why the experience in the literature with anakinra is more substantial than with canakinumab. By analyzing studies in which patients have switched from one treatment to another, it seems that the main reason for switching is the ease of administration of canakinumab and/or the loss of compliance to anakinra after longer periods of use (36,43,56,61,64,66,72). A second reason for switching from anakinra to canakinumab is the occurrence of injection site reactions or other side effects with anakinra (such as urticaria or the rise of liver enzymes) which seem less prominent when taking canakinumab (40,42,43).…”
Section: Anakinra Vs Canakinumabmentioning
confidence: 99%